Typography on the Horizon of Art - Szlama, Norbert (ARTCADIA, 2023)
The primary function of typography defined from a semiotic point of view is information encoding; this basic function is strengthened, broadened or in some cases abandoned by art. Theo Van Leeuwen repeatedly indicated in his research that letters carry meaning beyond the semiotic definition. This was examined in a narrower segment by Johanna Drucker, who explored experimental typography in the light of modern arts (Futurism, Dada, Cubism). However, she interpreted this rather on the axis of the image poem from the perspectives of poetry and literature. This justified for me the fact that in my study I should examine the typography built into fine arts, the interpretation of the letter as an image. In my paper, I focus on the related artistic attitude, thus my central question can be properly articulated: Is it possible to extract the culturally rooted function of typography from a text that appears in a work of art, or does writing, as a new level of information communication, appear in visual arts through it?
Keywords: typography; avant-garde; cubism; futurism; dada; contemporary